INSANUS HOMERUS? CRÍTICA LITERARIA E HISTORIAS DE TROYA ENTRE PROSA Y POESÍA - de Carlos Villamarín, Helena (Exemplaria Classica, 2016)
Two XIIth. century poems, the Anonymi Historia Troyana Daretis Phrigii, and the Ilias of Joseph of Exeter, reproduce the controversy depicted by Cornelius in his prologue to the book of Dares between his true account of the Trojan war and that of Homer. Medieval poets have properly understood a debate which was common in Ancient criticism and Homer’s function as a “theologian”.